(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2026)
The Laweyan district in Surakarta is formally designated as a cultural heritage precinct in accordance with the Regulation of the Minister of Culture and Tourism No. PM.03/PW.007/MKP/2010. Its distinctiveness is articulated through its historical significance, morphological characteristics, and socio-cultural dimensions. Between 1521 and 1546, Laweyan functioned as a perdikan territory, an autonomous enclave exempt from royal taxation, under the leadership of Kyai Ageng Henies. Within this historical framework, the Laweyan community developed a reputation for economic self-sufficiency, particularly as batik entrepreneurs, thereby reinforcing its contemporary identity as a Batik Village. The central issue addressed in this study is the absence of a comprehensive framework to guide the revitalization of the area, a condition that raises serious concerns regarding its sustainable development as a site of considerable historical value. Accordingly, the objective of this research is to formulate a set of revitalization guidelines for heritage areas that can function as a normative reference, ensuring that future interventions remain consistent with the regulatory provisions established in Law No. 11 of 2010. Methodologically, this study adopts a grounded theory approach. The collected data are systematically categorized and coded, followed by interpretative analysis grounded in the theoretical constructs of preservation, conservation, and revitalization. The findings of this research are intended to provide a structured guideline for the revitalization of the Laweyan district, thereby supporting its continued protection and development as a designated cultural heritage site.